Dietary selenium sources alleviate immune challenge induced by Salmonella Enteritidis potentially through improving the host immune response and gut microbiota in laying hens - Kang, Ruifen; Wang, Weihan; Liu, Yafei; Huang, Shimeng; Xu, Jiawei; Zhao, Lihong; Zhang, Jianyun; Ji, Cheng; Wang, Zhong; Hu, Yanxin; Ma, Qiugang (Frontiers in Immunology, 2022)
The aim of this study was to evaluate the effects of different selenium (Se) sources on the immune responses and gut microbiota of laying hens challenged with Salmonella Enteritidis (S. Enteritidis). A total of 240 45-week-old layers were randomly divided into 8 groups with 6 replicates per group according to 4×2 factorial design, including a blank diet without Se supplementation (CON group) and three diets with 0.3 mg / kg Se supplementation from sodium selenite (IS group), yeast Se (YS group), and selenium-enriched yeast culture (SYC group), respectively. After 8-week feeding, half of them were orally challenged with 1.0 mL suspension of 109 CFU/mL S. Enteritidis daily for three days. The serum was collected on 3, 7, 14 d, and the cecum content was collected on 14 d after challenge. There was no significant difference in laying performance among the eight groups before challenge. S. Enteritidis challenge significantly decreased the laying performance, egg quality, GSH-Px, IgG, IgM, and increased the ratio of feed and egg, MDA, Salmonella-specific antibody (SA) titers, IL-6, IL-2, IL-1β and INF-γ. However, SYC increased the level of GSH-Px, IgG and decreased IL-6, YS decreased the level of IL-2 and IL-1β. What’s more, Se supplementation decreased SA titers to varying degrees and reduced the inflammatory cell infiltration in the lamina propria caused by S. Enteritidis infection. In addition, S. Enteritidis challenge disrupted intestinal flora balance by reducing the abundance of genus Clostridium innocuum, Lachnospiraceae and Bifidobacterium, and increasing genus Butyricimonas and Brachyspira. While Se supplementation increased the gut microbial alpha diversity whether challenge or not. Under S. Enteritidis challenge condition, the alteration of microbial composition by the administration of different Se sources mainly manifested as IS increased the relative abundance of genus Lachnospiraceae and Christensenellaceae, YS increased the relative abundance of genus Megamonas and Sphingomonas, SYC increased genus Fusobacterium and Lactococcus. The alteration of gut microbial composition had closely relationship with antioxidant or immune response. To summarize, different Se sources can improve the egg quality of layers challenged by S. Enteritidis that involves elevating immunity and regulating intestinal microbiota.